2021
DOI: 10.1109/access.2021.3097436
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Machine Learning-Enhanced Channel Estimation for OFDM Systems

Abstract: Recently much research work has focused on employing deep learning (DL) algorithms to perform channel estimation in the upcoming 6G communication systems. However, these DL algorithms are usually computationally demanding and require a large number of training samples. Hence, this work investigates the feasibility of designing efficient machine learning (ML) algorithms that can effectively estimate and track time-varying, frequency-selective channels. The proposed algorithm is integrated with orthogonal freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…However, in [35], the theoretical Power Density Functions (PDFs) of misalignments and composite channel models were derived from approximation approaches, which resulted in some discrepancies with the experimental data, especially at the tails of the distributions. Such results support the assertion by the authors of [66] that utilizing Machine Learning (ML) algorithms offers a data-driven perspective that does not rely on channel statistics and approximations. This makes ML algorithms suitable for emerging and unique communication configurations where channel statistical modeling is challenging.…”
Section: Impact Of Atmospheric Turbulence Uav Vibration and The Role ...supporting
confidence: 85%
See 1 more Smart Citation
“…However, in [35], the theoretical Power Density Functions (PDFs) of misalignments and composite channel models were derived from approximation approaches, which resulted in some discrepancies with the experimental data, especially at the tails of the distributions. Such results support the assertion by the authors of [66] that utilizing Machine Learning (ML) algorithms offers a data-driven perspective that does not rely on channel statistics and approximations. This makes ML algorithms suitable for emerging and unique communication configurations where channel statistical modeling is challenging.…”
Section: Impact Of Atmospheric Turbulence Uav Vibration and The Role ...supporting
confidence: 85%
“…Essentially, it is important to understand which ML method is suited to the nature of the problem at hand, and for this reason, the authors of [70] exploited an extensive dataset for FSO links over a maritime environment to compare the prediction accuracy of different methods, determining that a shallow Artificial Neural Network (ANN) performed best. In [66], the authors also demonstrated the effectiveness of shallow ANNs over deep learning methods when constrained by a smaller training sample size. The effectiveness of ANNs was further shown by the authors of [71], who used a shallow Nonlinear AutoRegressive eXogenous (NARX) ANN to accurately estimate channel state using experimental data from an outdoor FSO link transmitting coherent signals.…”
Section: Impact Of Atmospheric Turbulence Uav Vibration and The Role ...mentioning
confidence: 97%
“…This approach might be seen as an ML interpolation strategy with results similar to the MMSE, and some other discussed NN. A proposed similar channel estimation method using a multiple variable regression approach to design an ML algorithm that does not require any initial information or statistics about the channel is found in [330]. It uses the SGD algorithm for parameter optimization purposes.…”
Section: Reduction Training Techniques For Neural Networkmentioning
confidence: 99%
“…Training datasets are created offline under various environmental conditions where the received signals are recorded and used as training data for the system to learn. Furthermore, ML can be used to estimate channel impulse response (CIR) coefficients for equalization purposes [14]. In the future, communication using the OFDM signal will be transmitted over the air, space, or underwater channels to create a fully connected world.…”
Section: For Channel Estimationmentioning
confidence: 99%